Competition Among Multiple Retailers within a Small and Fast Developing Economy - Urbonavičius, Sigitas; Brock, Gregory; Ivanauskas, Robertas (Ekonomika, 2006)
In the intensely competitive retailing sector of the new EU accession countries, retailers often compete on the basis of diversification or high growth. With high growth, discount pricing is the key. As new member countries often have households with a low purchasing power, price-based competition is widespread. However, as these economies grow, retailers will need to diversify away from simply a low price strategy. Using the case of Lithuania, a sample of multiple retailers is examined from the consumer perspective. Consumer loyalty. a multiple retailer’S image. differentiation and the idea of a purchasing occasion appear to be where retailers should focus as they move away from a narrow low price strategy.